Metaverse entrepreneurship : analysis of Zielo Studio - Bonato, Pietro (2023)
During the eighth edition of Facebook Connect in 2021, Mark Zuckerberg announced the group's rebranding as Meta. "This is not the way we are meant to use technology", said Zuckerberg referring to how people are used to experiencing digital resources nowadays (Zuckerberg, 2021). This annual conference not only marked the centrality of the Metaverse for Meta’s strategy. It also announced its disruptive potential to the world. Meanwhile, in 2021 a groundbreaking Amsterdam-based startup was born. Zielo Studio, established by Laura Kyttanen, today is positioned at the forefront of reshaping the dynamics of team interactions in the modern workplace. The company was founded on the principles of conscious leadership and equipped with a pioneering Metaverse-based coaching model. Laura’s mission is to revolutionize the coaching industry by supporting positive transformation in teams and workplace cultures, and the Metaverse brilliantly serves to convey this vision. This thesis aims to uncover the importance of the Metaverse as a transformative phenomenon in an industry. It will also analyze the different challenges brought by the adoption of such an innovative technology from the point of view of a young startup. From a literature review to interviews with the founder, this thesis unfolds to offer multiple reads on diverse topics. Finally, it will be presented to its readers as an engaging case study, based on concrete examples. This will allow an in-depth analysis of real-world scenarios, providing formative insights for business students and future entrepreneurs.